The Importance of Multicultural Education at an Early Age in Indonesia - Susanto, Erwin; Putri Saylendra, Nadya; Susanti, Neneng (International Journal of Psychosocial Rehabilitation, 2020)
This article is made to identify the importance of multicultural education in early childhood in Indonesia. Multicultural education can be regarded as human beings who wanted education to accept and understand that the difference is the gift of God Almighty. Indonesia has a very high level of diversity, such as the diversity of race, religion, culture and customs. Based on literature reviewed, this article gives the results of how the importance of implementing multicultural education based on early childhood in Indonesia. For the long-term impact, it is very useful for the development of Indonesian human characters who love peace and mutual tolerance for differences.